2014
DOI: 10.1186/bf03352196
|View full text |Cite
|
Sign up to set email alerts
|

Some remarks on the origin of seismic anisotropy in the D” layer

Abstract: Physical mechanisms of seismic anisotropy in the D" layer are examined based on seismological and mineral physics observations. The results of body-wave seismology on the fine structure of the D" layer and of mineral physics studies on the elastic constants and the lattice preferred orientation in lower mantle minerals as well as the shape preferred orientation of melt pockets are taken into account. Evidence of large but depth (pressure)-dependent elastic anisotropy of lower mantle minerals, particularly (Mg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 53 publications
1
58
0
Order By: Relevance
“…The consensus from these studies is that SPO-type models generally do a good job of matching the seismological constraints. Models that invoke the LPO of lowermost mantle minerals can also plausibly explain splitting observations in D 00 if deformation is being accommodated via dislocation creep (e.g., Karato 1998). A recent review of experimental constraints on LPO in lowermost mantle minerals can be found in Yamazaki and Karato (2007) and we provide only a brief summary here.…”
Section: The D 00 Regionmentioning
confidence: 96%
See 1 more Smart Citation
“…The consensus from these studies is that SPO-type models generally do a good job of matching the seismological constraints. Models that invoke the LPO of lowermost mantle minerals can also plausibly explain splitting observations in D 00 if deformation is being accommodated via dislocation creep (e.g., Karato 1998). A recent review of experimental constraints on LPO in lowermost mantle minerals can be found in Yamazaki and Karato (2007) and we provide only a brief summary here.…”
Section: The D 00 Regionmentioning
confidence: 96%
“…In contrast to the overlying lower mantle, observations of seismic anisotropy in the D 00 layer at the base of the mantle are abundant, and both SPO-and LPO-type models have been proposed (e.g., Kendall and Silver 1998;Lay et al 1998;Karato 1998). Models that invoke SPO as a mechanism for generating anisotropy in D 00 rely on the presence of a material in the lowermost mantle with elastic properties that sharply contrast with the surrounding matrix.…”
Section: The D 00 Regionmentioning
confidence: 99%
“…Not only does (Mg, Fe)SiO 3 perovskite have a lower intrinsic anisotropy than (Mg, Fe)O [Stixrude, 1998], but it is likely that (Mg, Fe)O is the weaker phase [Yamazaki and Karato, 2001] and undergoes significantly more strain than (Mg, Fe)SiO 3 perovskite in the two-phase system. Moreover, fabric experiments on perovskite analog materials indicate a lower degree of anisotropy exhibiting V SV > V SH anisotropy for horizontal shear [Karato, 1998a;Yamazaki and Karato, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…[4] Possible causes of D 00 anisotropy are discussed by Karato [1998aKarato [ , 1998b, Lay et al [1998aLay et al [ , 1998b, and Kendall [2000]. On one hand, SPO can result from oriented melt inclusions or heterogeneous material with a large contrast in elastic constants.…”
Section: Observations and Causes Of Anisotropymentioning
confidence: 99%
See 1 more Smart Citation